Szanse i zagrożenia polskiego sektora owczarskiego w okresie integracji z Unią Europejską - Rokicki, Tomasz (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2007)
In the paper opportunities and threats of polish sheep’s sectors during integration with European Union was presented. Integration with European Union has made many opportunities and threats. Opportunity is capability use with direct disbursement and structural funds. Big threats for sheep production were decrease and resigning from national grant. Big chance will be creation national sheep meat market